Análise do comportamento de pilares mistos aço-concreto em situação de incêndio - Ana Paula Mendonca Nobrega (2003)
It is known that the use of composite columns made of totally and partially encased steel sections or composite columns made of concrete filled hollow sections is a quite consolidated structural system to civil construction in Brazil and the whole world. In general, a composite column must be designed at room temperature and under firecondition using appropriate standards and specifications. The most problem to design composite column in fire condition is the temperatureredistribution in cross-section (steel profile, concrete and reinforcing bars together) that is a function of the time of fire exposure. In fact, this problem is normally solved with simplified design methods that present tables with the resistance of composite columns or some tables with average temperature in cross-section in fire condition and parameters that determine the resistance and the stiffness of the composite column.This work presents a critical analysis of simplified design methods according EC4- Part 1.2 (1994), using a software based on the finite element method developed in Federal University of Minas Gerais for bidimensional thermal analysis to composite columns made of partially encased steel sections or composite columns made of concrete filled circular hollow sections under axial compression.